2005
DOI: 10.1038/sj.bmt.1705238
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of alloreactive T cells via CD69: implications on antiviral, antileukemic and immunoregulatory T lymphocytes

Abstract: Selective depletion of alloreactive T cells from stem-cell allografts should abrogate graft-versus-host disease while preserving beneficial T cell specificities to facilitate engraftment and immune reconstitution. We therefore explored a refined immunomagnetic separation strategy to effectively deplete alloreactive donor lymphocytes expressing the activation antigen CD69 upon stimulation, and examined the retainment of antiviral, antileukemic, and immunoregulatory T cells. In addition to the CD69 high T cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…CD69 is not an appropriate marker for specifically activated Treg cells as it can also be increased by cytokines in a bystander fashion [30]. In addition, both markers are not specifically expressed on Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD69 is not an appropriate marker for specifically activated Treg cells as it can also be increased by cytokines in a bystander fashion [30]. In addition, both markers are not specifically expressed on Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Sagoo et al suggested that the upregulation of CD69/CD71 on Treg cells after an allogeneic activation can be used for the isolation of Ag-specific Treg cells [29]. CD69 is not an appropriate marker for specifically activated Treg cells as it can also be increased by cytokines in a bystander fashion [30]. In addition, both markers are not specifically expressed on Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell preparations are purged of alloreactive donor T cells by activation in mixed lymphocyte reaction against host stimulators, followed by depletion with immunotoxins, immunomagnetic selection, or FACS, all of which exploit expression of cell surface activation markers (CD25, CD69, CD134, CD137, CD147, and HLA-DR). [59][60][61][62][63] Other methods include FasL-mediated killing of activated T cells, 64 apoptosis induction by heat shock protein 90 (HSP 90), 65 or anergy induction by costimulatory blockade. 66 The anti-CD25 antibody conjugated to ricin toxin was first used in pediatric patients with immune deficiencies.…”
mentioning
confidence: 99%
“…18 Various approaches have been developed, including the transfer of purified memory T cells 19,20 or the in vitro depletion of allo-reactive T cells stimulated with recipient antigen-presenting cells. [21][22][23] Similarly, in vitro stimulation of allo-reactive T cells in the presence of co-stimulation blockade was used to induce T-cell anergy. 24 An elegant alternative to the in vitro depletion of allo-reactive T cells is the introduction of 'suicide genes' that can be triggered in vivo in patients developing GvHD after T-cell transfer.…”
Section: Discussionmentioning
confidence: 99%